COUPLED FIELD ANALYSIS OF PIEZOELECTRIC CANTILEVER BEAM - Kunal Ganpati Rajdeep (International Journal of Innovations in Engineering Research and Technology, 2021)
Electromechanical modelling efforts in the research field of vibration-based energy harvesting have been mostly focused on forms of vibrational input as in the typical case of harmonic excitation at resonance. However, ambient vibrational energy often has broader frequency content than a single harmonic. Piezoelectric energy harvesting is a promising technology for extracting the power from environmental vibrations. It generates the electrical power of few orders of amplitudes which is sufficient to drive several autonomous electrical devices. Such vibration-based energy harvester generates the most energy when the generator is excited at its resonance frequency. Simplest model to be started is of rectangular Aluminium cantilever beam with unimorph piezoelectric patch which is perfectly bonded to the substrate plate at the end.